The influence of country-of-origin effects on portuguese consumers purchase intention: the chinese mobile phone brand - Ding, Ying (2021)
In the international market, the country of origin exerts a very important impact on consumer behavior. At present, China's economy still maintained a relatively stable development, "made in China" break into people's daily lives all over the world. At present, China's trade exports to Portugal are also growing rapidly, and Chinese mobile phone brands such as Huawei, Xiaomi and OPPO also have entered the Portuguese mobile phone market in succession, and with sales increasing year by year. Based on the market survey of Portuguese consumers, this dissertation studies Portuguese consumers' perception and purchase intention towards Chinese brand mobile phone. On the basis of combing the relevant theories with a survey of 260 Portuguese consumers, this dissertation discusses the perception of mobile phone brand from China by the Portuguese consumers and their purchase intention, as well as the relationship between perception and purchase intention. The data collected were analyzed by variance analysis, correlation analysis, regression analysis and other statistical methods. And the conclusion is as followed: Country of origin has impact on the perceived value of Portuguese consumers towards Chinese brand mobile phone and further influences their purchase intention. Even though it has been proven by research and methodologies that the consumers could evaluate all the intrinsic characteristics of mobile phone by experiencing it personally, however extrinsic cues such as Country of origin still plays an important role in their judgement. During the process of purchasing decision, functional value has mediation effects on Portuguese purchase intention. Compared with the lower income family and limited education people, the people from higher income family and with higher education background will be less likely been influenced by the Country of origin.